Communication Strategies in Legal Crisis Management: Analysis of International Cases - Roberto Fabián Sánchez Chávez , Jorge Armando Mendoza Hernández, Luis Edison Torres Alulema (Journal of International Crisis and Risk Communication Research, 2024)
Legal crises represent significant challenges for organizations, requiring effective communication strategies to mitigate reputational impacts. This article analyzes communication strategies implemented in recent international cases of legal crises, highlighting their effectiveness and lessons learned. Through a qualitative approach, landmark cases were reviewed over the past five years, identifying key patterns and their impact on public perception. The results reveal the importance of transparency, narrative control and the use of digital platforms as essential tools for the management of legal crises. This analysis provides a framework for strengthening corporate communication capacities in critical contexts.